Managerial Perceptions on Internal Marketing and Employee Commitment in Nepal - Shrestha, Prakash (Journal of Balkumari College, 2020)
The major purpose of this study is to examine the managerial perceptions on internal marketing and employee commitment in Nepal. This is a qualitative research in nature. It covers management-level employees of covers 30 organizations (including 14 commercial banks and 16 insurance companies) of Nepal. This study is based on discussions with 30 managers ((division chiefs, branch managers, human resource managers, department heads, IT managers, branch managers, officers and managers) of Nepalese commercial banks and insurance companies by using semi-structured interviews and discussions. The results of present study show that the managers are conscious about internal marketing and employee commitment in their organizations. They also realized the important factor of these components. It is suggested that management should be aggressively engaged in internal marketing to arrive at a synergy of satisfied employees and promoted employee commitment. Committed, satisfied and competent employees will make a better impression on customers, benefiting the organization as a whole.